Magnetic resonance imaging as a prognostic disability marker in clinically isolated syndrome: A systematic review. (6th September 2018) - Rahn, Anne C.; Köpke, Sascha; Stellmann, Jan‐Patrick; Schiffmann, Insa; Lukas, Carsten; Chard, Declan; Heesen, Christoph
Abstract : Magnetic resonance imaging (MRI) is the key prognostic tool in people with a clinically isolated syndrome (CIS). There is increasing interest in treating people following a CIS in the hope that conversion to multiple sclerosis (MS) will be prevented and future disability reduced. So far, the prognostic value of MRI for disability following a CIS has not been evaluated systematically. We systematically searched MEDLINE and EMBASE. Cohort studies were selected if they reported associations of MRI and disability following a CIS, included at least 50 people with a CIS at baseline, had at least 5 years of follow‐up and obtained at least one structural MRI measurement (T1 lesions, T2 lesions, T1 contrast‐enhancing lesions or brain atrophy). We assessed the studies for quality and rated the completeness of MRI reporting. In total, 13 studies were identified reporting on the following: T2 lesion number and volume, T2 infratentorial lesion number and volume, T1 contrast‐enhancing lesions and grey matter fraction. T2 brain lesion number determined soon after the occurrence of a CIS was associated with disability progression after 5‐7 years, with an increased risk when 10 or more lesions were present. Infratentorial lesions were also associated with a higher risk of subsequent disability. The number and distribution of MRI‐visible lesions soon after a CIS are associated with disability later on, and may offer additional useful information when making treatment decisions in people with early MS. Further work is required to determine whether other measures have a higher predictive potential.